Success Factors of Electronic (E) Agriculture in Ghana: Lessons from MoFA and Cowtribe (Ghana Journal of Science, Technology and Development, 2023)
The productive potential of digital technologies has been articulated in various sectors of the economy and found expression in electronic agricultural extension, otherwise known as e-extension. E-extension has been described as holding the promise of resolving communication and extension challenges confronting the agricultural sector. The government of Ghana, through the Ministry of Food and Agriculture, the World Bank, and the Food and Agriculture Organization (FOA), have all recommended and supported initiatives on e-extension in Ghana. The WSIS 2010 plan of action includes e-agriculture as an area of application of ICTs in enhancing agricultural productivity. The emerging discourses around ICT and agriculture are also against a backdrop of research evidence that radio remains the most used means of accessing agriculture information among Ghana's farmers.  Therefore, this study focuses on Ghanaâ€™s experience with e-agriculture to investigate the opportunities and challenges of applying the concept. The paper examines principles defining success factors of Ghana's e-extension initiative using Cowtribe, a private sector initiative, and government e-extension. Results of the study show that while MoFA's e-extension initiatives have had challenges in reaching farmers efficiently, Cowtribe represents the progress and success story of e-agricultural extension in Ghana by providing essential and timely information on livestock management and agricultural market data services, respectively, to farmers and other value chain actors. The study results are expected to contribute theoretical insights into the opportunities and challenges of using ICT in agricultural extension.Key Words: e-agriculture, ICTs, Cowtribe, agricultural extension, digital space